PROGRAM PENDAMPINGAN PENINGKATAN EFEKTIFITAS SISTEM PEMBERIAN KREDIT PADA LPD DESA BURUAN DI KABUPATEN TABANAN - I.A Putu Widani Sugianingrat; I.A, Ketut Surya Wahyuni; Putu Sri Hartati (UNHI Press, 2021)
The Village Credit Institution (LPD) is one of the assets and sources of income for the Pakraman village that requires good management by the management and supervisory body. So that the LPD is not eroded by the era of globalization, the LPD must adhere to the principles of prudence and honesty from the financial manager. In providing loan or credit capital to the community, the LPD at least has definite criteria for the prospective credit recipients themselves. This is because offering such capital must have reciprocity that will help the LPD sustain. Credit system analysis that has been carried out by LPDs has only been in the form of analysis of the stage of the prospective customer. so that the implementation of the credit-giving system by LPDs is less than optimal. If this is done continuously, it will certainly have an impact on the quality of credit extended and increase the potential for non-performing loans. The solution that can minimize these problems is to provide socialization and assistance in terms of increasing the effectiveness of credit extension according to the 5C and 7P principles. The method of implementation is carried out by observation and discussion with the Head of the LPD, providing an overview of the urgency of financial management in helping to implement a more effective credit system, helping LPD management to cope with the implementation of a credit system according to the 5C and 7P principles. This stage also involves a comparison of the credit estimates that were previously run with the old system with the new system. The final result of this activity, it is hoped that the LPD will be able to implement new / complete guidelines containing the stages which are the procedures for providing effective credit, assessing the feasibility of a credit application with the precautionary principle to minimize the implementation of bad credit.